STUDI LITERATUR : PENGEMBANGAN MODUL COMPUTATIONAL THINKING BERBASIS QUANTUM TEACHING AND LEARNING (QTL) UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KOMPUTASI SISWA KELAS 4SDICT AL ABIDIN SURAKARTA - Ayu Oktavia Rosanti; Sunardi, Roemintoyo (Prosiding Seminar Nasional Indonesia, 2024)
This research aims to look at the development of computational thinking-based modules based on Quantum Teaching and Learning (QTL) in improving students' computational thinking skills in terms of literature study. This research is development research using the RnD and 4D Model approaches as well as the Quantum Teaching and Learning (QTL) approach as the basis for module development. QTL is a learning approach model that emphasizes that learning must be fun and take place in a happy environment. This model assumes that the entry of information will be more comprehensive and well recorded. The sample for this research was 69 grade 4 students at SDICT Al Abidin Surakarta. Consisting of class 4A Ibnu Majah 25 students, class 4B Ibnu Nafis 20 students, and class 4C Ibnu Abbas 24 students. The results of this research are that the computational thinking teaching module developed through the QTL approach can improve students' computational thinking skills optimally and the results of the literature study show that the four research journals used in this research produce the feasibility of using the module both for teaching in the classroom for teachers and as a guide or Student guidelines in computational thinking subjects in improving critical thinking skills, especially for SDICT Al Abidin Surakarta.